2012
DOI: 10.1245/s10434-012-2325-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism and Negative Tc99 Sestamibi Imaging: To Operate or Not?

Abstract: A curative operation is performed at an acceptably lower rate with negative MIBI imaging. A decision for surgery with a negative MIBI finding should consider lower cure rates and symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 22 publications
8
49
0
1
Order By: Relevance
“…In our series, the incidence of MGD was 18%, which was within the range of 3-24% reported in the literature (20). The rate of MGD in cases of negative PS has been reported as w25% (21,22,23). Therefore, negative localization with sestamibi infers a highly selected patient population with small parathyroid adenomas and/or MGD.…”
Section: European Journal Of Endocrinologysupporting
confidence: 78%
See 1 more Smart Citation
“…In our series, the incidence of MGD was 18%, which was within the range of 3-24% reported in the literature (20). The rate of MGD in cases of negative PS has been reported as w25% (21,22,23). Therefore, negative localization with sestamibi infers a highly selected patient population with small parathyroid adenomas and/or MGD.…”
Section: European Journal Of Endocrinologysupporting
confidence: 78%
“…Therefore, negative localization with sestamibi infers a highly selected patient population with small parathyroid adenomas and/or MGD. It has been shown that the cure rate was lower in this subgroup of patients (21,22). It is currently accepted that besides some cellular-molecular specificities, one possible explanation for decreased detection of MGD (often hyperplasic) is related to their smaller volume compared with adenomas.…”
Section: European Journal Of Endocrinologymentioning
confidence: 81%
“…5 In the last 30 years, the wide use of the multichannel autoanalyzer; use of USG, MIBI, computed tomography (CT), and MRI for the diagnosis of PHPT; and new surgical methods and techniques for the surgical treatment of PHPT have resulted in easier diagnosis of the disease, correct localization of pathologic lesions, and different surgical approaches. 1,[5][6][7][8][9][10][11][12][13][14][15][16][17] The aim of this study was to present our 20-yearexperience with 190 patients diagnosed with PHPT, their clinical features, diagnostic methods, surgical treatment and pathology, and review of the literature.…”
mentioning
confidence: 99%
“…These new imaging and diagnostic methods include USG, MIBI scintigraphy, MRI, MIBI scintigraphy with the use of CT, and intraoperative adjuncts, such as a gamma probe with radioisotope sestamibi, intraoperative rapid PTH measurements, and the use of methylene blue or frozen section. [5][6][7][8][9][10][11][12][13][14][15][16][17] USG is a cheap, adequate, and noninvasive modality. Sensitivity of USG is associated with the user, the size and localization of the adenoma and concomitant thyroid disorder.…”
mentioning
confidence: 99%
“…En nuestra experiencia, el porcentaje de FN del cintigrama paratiroideo en pacientes con HPP confirmado bioquímicamente, fue similar a lo descrito en otras publicaciones 12,13 . El factor más comúnmente reportado como causa de falsos negativos es el tamaño de la glándula paratiroidea.…”
Section: Discussionunclassified